(untitled) (Tempo e Argumento, 2021)
This article analyzes how a group of 9th Grade students from a public school represents time in the history taught in the classroom. A questionnaire was applied during the activities carried out under the Brazilian Institutional Teaching Initiation Scholarship Program (Programa Institucional de Bolsas de Iniciação à Docência [PIBID]) at the School of History (Faculdade de História [FAHIST]) of the Federal University of Southern and Southeastern Pará (Universidade Federal do Sul e Sudeste do Pará [UNIFESSPA]), through which students were able to register an information set on History teaching, especially regarding its relationship with the understanding of time. Starting from the records produced by students, it was noticed that the history taught is predominantly related to the past, with virtually no link or relationship with the present and no connections with future prospects.. Keywords: History; teaching; time; basic education